2014
DOI: 10.1097/yct.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging Changes Subsequent to Electroconvulsive Therapy in Unipolar Depression

Abstract: Electroconvulsive therapy (ECT) is an effective treatment for major depressive episodes; however, the neural mechanisms underlying its therapeutic effects remain largely unknown. This review summarizes the findings of functional neuroimaging studies on the effects of the ECT treatment in patients with unipolar depression. Functional neuroimaging studies show that ECT induces changes in cerebral metabolism, blood flow, neurotransmitter activity, neuronal metabolites, and brain functional connectivity. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…ECT‐induced seizures spread from the initiation site to other brain regions and decrease cerebral blood flow (CBF) to the left dorsolateral frontal cortex and bilateral cingulate gyrus, which suggests that this propagation occurs through cortical‐cortical or cortico‐thalamo‐cortical networks . Although, the precise mechanisms of action are unknown, PET and single‐photon emission computed tomography studies have shown that ECT changes neurotransmitter activity, brain functional connectivity, CBF, and cerebral metabolism . PET uses positron‐emitting radiotracers such as 18 F‐2‐fluoro‐2‐deoxy‐d‐glucose, a glucose analogue, and [ 15 O]H 2 O to measure cerebral glucose metabolism (CMRglu) and CBF, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECT‐induced seizures spread from the initiation site to other brain regions and decrease cerebral blood flow (CBF) to the left dorsolateral frontal cortex and bilateral cingulate gyrus, which suggests that this propagation occurs through cortical‐cortical or cortico‐thalamo‐cortical networks . Although, the precise mechanisms of action are unknown, PET and single‐photon emission computed tomography studies have shown that ECT changes neurotransmitter activity, brain functional connectivity, CBF, and cerebral metabolism . PET uses positron‐emitting radiotracers such as 18 F‐2‐fluoro‐2‐deoxy‐d‐glucose, a glucose analogue, and [ 15 O]H 2 O to measure cerebral glucose metabolism (CMRglu) and CBF, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Although, the precise mechanisms of action are unknown, PET and single-photon emission computed tomography studies have shown that ECT changes neurotransmitter activity, brain functional connectivity, CBF, and cerebral metabolism. 6,7 PET uses positronemitting radiotracers such as 18 F-2-fluoro-2-deoxy-dglucose, a glucose analogue, and [ 15 O]H2O to measure cerebral glucose metabolism (CMRglu) and CBF, respectively. 8,9 Changes in CMRglu and CBF after a course of ECT have been inconsistent between studies, primarily due to methodological limitations and the heterogeneity of disorders.…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, it is necessary to conduct systematic review and meta-analysis for ECT-related effects on brain structures. Currently there are several narrative or systematic reviews of neuroimaging studies related to ECT, [13][14][15][16] but only one metaanalysis has been published so far, that by Wilkinson et al who reported that ECT increased bilateral hippocampal volume. 17 Unfortunately, they did not include the largest study currently available, 18 and focused only on hippocampal volume.…”
mentioning
confidence: 99%
“…In studies of changes in blood flow after ECT, findings are, however, even more divergent and inconsistent (Zhuo and Yu 2014). There are several suggested explanations for this, besides the impact of timing of post-ECT scanning discussed above.…”
Section: Significant Shifts In Perfusion Ratios After Ectmentioning
confidence: 89%